Current Understanding of the Acute Exacerbation of Chronic Rhinosinusitis - Wu, Dawei; Bleier, Benjamin Saul; Wei, Yongxiang (Frontiers in Cellular and Infection Microbiology, 2019)
Background: Acute exacerbations of chronic rhinosinusitis (CRS) have been increasingly recognized as a significant disease form with a significant impact on quality of life in the clinic setting. There is a growing amount of research on the etiopathogenesis and management of acute exacerbations of CRS. The aim of this review is to summarize the current literature and provide an overall understanding of acute CRS exacerbations. Methods: A related literature review with the key terms of “chronic rhinosinusitis” and “exacerbation” was performed using PubMed. Results: There is no consensus definition of the acute exacerbation of CRS. Impaired mucociliary clearance, atrophic rhinitis, and immunologic changes are important predisposing factors for acute CRS exacerbations. Current evidences support the role of the transient viral infection as the initial inflammatory stimulus in the pathogenesis of acute CRS exacerbations. Secondary bacterial infection or microbial community dysbiosis within sinonasal cavity are the main event during the acute exacerbation of CRS. Distinct changes in local and systemic immune responses during exacerbation provide new insights into the pathophysiology of CRS exacerbation. Although current guidelines suggest the use of short-term antibiotics in patients with acute CRS exacerbation for symptomatic relief, evidence‐based treatment recommendations for acute CRS exacerbation are still lacking and large high-quality RCTs are required. Conclusion: There have been significant advances in understanding the etiology and immunological feathers of acute CRS exacerbation. Nevertheless, consensus definition, diagnostic criterion, biomarkers to differentiate acute CRS exacerbation from CRS, assessment of disease severity, and evidence-based treatment options for acute CRS exacerbation are still lacking.